Readiness and Implementation of The Merdeka Curriculum in Accounting and Financial Institution Vocational Program A Case Study of State Vocational High School 1 Dumai City - Sukoco, Hanifah Indriyani; Jatmika, Surya (Proceedings International Conference on Education Innovation and Social Science, 2024)
This study aims to determine the readiness and implementation of the Merdeka curriculum in the Accounting and Financial Institution Expertise Program at State Vocational High School 1 Dumai City. The research uses a qualitative approach with a case study design. The subjects of this study consist of the principal of State Vocational High School 1 Dumai City, the vice principal for curriculum, the head of the Accounting and Financial Institution Expertise Program, and 2 students from grade X and grade XI. The data collection techniques used are interviews, observation, and documentation. The data validity techniques use source triangulation and technique triangulation. The data analysis technique uses interactive data analysis, which includes data condensation, data presentation, and conclusion drawing and verification. The results of this study are as follows: 1) The readiness for implementing the Merdeka curriculum at the Center of Excellence Vocational High School includes facilities and infrastructure such as computer laboratories, classrooms, teacher rooms, vocational competence practice facilities, projectors, the UKS room, and organic and non-organic waste disposal facilities. Teacher and educational staff preparation, as well as curriculum implementation mentoring activities, are also included, with training/workshops to enhance teachers and GTK, as well as learning tools. 2) The implementation of the Merdeka curriculum at the Center of Excellence Vocational High School has been carried out from grades X to XII. IT and digital-based learning has been implemented, including the use of Google Classroom, Zoom application, and Quizizz, as well as learning using laptops, books, and projectors. The learning models used are Problem Based Learning and Project Based Learning. The implementation of the Professional Certification Institute (LSP) and Competency Skills Exams (UKK) is conducted in grade XII. 3) The obstacles in implementing the curriculum include a lack of understanding of the Merdeka curriculum and insufficient facilities and infrastructure, such as inadequate laboratories and shared projectors.